Disulfide-gated mesoporous silica nanoparticles designed for two-photon-triggered drug release and imaging. Issue 31 (13th July 2015) - Croissant, Jonas G.; Qi, Christian; Mongin, Olivier; Hugues, Vincent; Blanchard-Desce, Mireille; Raehm, Laurence; Cattoën, Xavier; Wong Chi Man, Michel; Maynadier, Marie; Gary-Bobo, Magali; Garcia, Marcel; Zink, Jeffrey I.; et al.
Abstract : We report two-photon cancer cell killing through mesoporous silica nanogates. Abstract : We report a two-photon-actuated cancer cell killing system that kills the cancer cells via drug delivery through multifunctional mesoporous silica nanogates. Two-photon-sensitive mesoporous organosilica (M2PS) nanocarriers were synthesized via the co-condensation of a silica precursor and a two-photon electron donor. The nanogates were constructed using a fast one-pot process at room temperature on the drug-loaded M2PS nanoparticles (NPs) with the bis(3-triethoxysilylpropyl)disulfide precursor. One and two-photon-actuated cargo releases from the M2PS nanogates were successfully monitored in aqueous solutions. Furthermore, the cellular uptake in MCF-7 cells was demonstrated via two-photon fluorescence imaging of the NPs, which were then applied successfully for drug delivery in cells.